Distortions of the discrete frequency-keyed signals with the linear frequency-modulated impulses in the antenna array - E. N. Builou; S. A. Gorshkov; V. A. Kondratyonok; M. M. Kasperovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Singularities of influence of distortions caused by object rotation, change of its sizes and nonlinearity of transceiver paths of the antenna array on results of handling of the discrete is frequency-keyed signals in broad-band radar-tracking systems of spatio-temporal handling are considered. Variants of compensating of the given types of distortions in the linear antenna arrays are offered.